Las variaciones de Hegel : sobre la "Fenomenología del espíritu" - Jameson, Fredric (Cuestiones de antagonismo ;, 2015)
In this major new study, philosopher and cultural theorist Fredric Jameson offers an innovative reading of a book that forms part of the bedrock of modern Western thought Hegers Phenomenology of Spirit.